Chaco-ban: the revolutionary of eco-charcoal / Iqbal Zharfan Masrul Hasdi ... [et al.] - Masrul Hasdi, Iqbal Zharfan; Dzulkifli, Mohamad Dzulhisyam; Mansor, Muhammad Aliff Daniel; Mohd Zokeri, Muhammad Azri Khir; Muhammad Dzahir, Muhammad Danial Azeem (2020)
Applications of charcoal have become an interest in daily life such as fuel for combustion. However, the commercial charcoal is normally produced by cutting the mangroves trees which are not sustainable and reduced a natural barrier against erosion, storm and floods. Hence, a new eco-friendly homemade charcoal was produced to replace the commercial charcoal. The new ChaCO-Ban material was produced by twosteps conventional pyrolysis methods involving daily waste materials such as orange peels, banana peels and paddy husk. The scanning electron microscope (SEM) images showed that the number of air cavities in the ChaCO-Ban sample is higher compared to the commercial charcoal. Sample with higher air cavity numbers is believed to produce more ignitions due to the higher oxygen levels around the sample. The energy dispersive X-Ray spectroscopy (EDS) results indicated higher ignition elements in the ChaCO-Ban sample compared with the commercial sample. The pH 9.4 of ChaCO-Ban sample is alkali and can neutralize the pH value of soil.